Detection of a photostable five-coordinate heme a3-Fe-Co species and functional implications of His384/α10 in CO-bound ba 3-cytochrome c oxidase from Thermus thermophilus - Pinakoulaki, Eftychia; Ohta, Takehiro; Varotsis, Constantinos (My University, 2004)
Resonance Raman (RR) spectra are reported for the fully reduced carbon monoxy derivative of ba3-cytochrome c oxidase from Thermus thermophilus. The RR spectra show the formation of a photolabile six-coordinate heme-CO and a photostable five-coordinate heme Fe-CO species. The latter species is formed by the cleavage of the proximal heme Fe-His384 bond and is the first five-coordinate Fe-CO species detected in heme-copper oxidases. The frequency of the Fe-CO species observed at 526 cm-1 correlates with either the C-O stretching modes observed at 1967 or 1982 cm-1 and lie on the correlation line of v(Fe-CO) vs v(C-O) for all known five-coordinate heme Fe-CO complexes. The loss of intensity of the heme Fe-His384 mode observed at 193 cm-1 in the photostationary CO-bound spectra is attributed to the loss of the non-hydrogen bonded heme Fe-His384⋯Gly359 conformer. Taken together, the data indicate that the environment of the ruptured His384 that is a part of the Q-proton pathway and leads to the highly conserved among all heme-copper oxidases, H2O pool, is disrupted upon CO binding to heme a3
Keywords: Stereochemistry; Cadmium compounds; Carbon monoxide; Copper; Enzymes; Iron compounds; Mercury compounds; Molecules; Spectroscopy; Quartz